HUKUMAN QISAS BAGI KES-KES YANG MELIBATKAN WANITA MENURUT HUKUM JENAYAH ISLAM - Ismail, Paizah (Jurnal Syariah, 2019)
There are two types of punishment for qi~a~ (retaliation) i.e. killing or huning. Islam has distinguished that punishment to be imposed on women whether they were victims or murderer. This article aims to elaborate this matter by referring to views of different madhhab and attempts to find a conclusive stand of Islam.